Peran Pembelajaran Berbasis Proyek dalam Meningkatkan Kualitas Keterampilan Siswa dalam Praktik Ibadah pada Mata Pelajaran Fikih Kelas VI di MI Muhammadiyah Gedongan - Sangadah, Siti; Subando, Joko (TSAQOFAH, 2025)
This study aims to describe the role of Project-Based Learning (PjBL) in enhancing students’ practical worship skills in the Fikih subject for Grade VI at MI Muhammadiyah Gedongan, Karanganyar. The research is motivated by the predominance of conventional teaching methods in Fikih instruction, which often focus on memorization and lectures, thereby limiting students’ mastery of practical worship skills. A descriptive qualitative approach was employed, with data collected through participatory observation, in-depth interviews, and documentation. Research subjects included the teacher and Grade VI students, and data were analyzed thematically with validity ensured through source triangulation. The findings indicate that the implementation of PjBL improves students’ ability to accurately perform religious practices such as wudhu, salat, and tayammum, while also fostering active participation, learning motivation, group collaboration, and spiritual awareness. Despite challenges such as limited time and facilities, the application of PjBL proved effective due to strong teacher engagement and a supportive madrasah environment. Thus, project-based learning is relevant for developing students’ worship skills and aligns with the goals of the Kurikulum Merdeka and the formation of the Pancasila Student Profile.